Persistent pollen exposure during infancy is associated with increased risk of subsequent childhood asthma and hayfever. Issue 3 (17th February 2013) - Erbas, B.; Lowe, A. J.; Lodge, C. J.; Matheson, M. C.; Hosking, C. S.; Hill, D. J.; Vicendese, D.; Allen, K. J.; Abramson, M. J.; Dharmage, S. C.
Summary Background Few studies have focused on pollen exposure and asthma in children. None have examined associations between persistent exposure to pollen in infancy and aeroallergen sensitisation and asthma in childhood. Objectives To examine the association between higher ambient levels of pollen in the first 3–6 months of life and risk of eczema, sensitization to food and aeroallergens at 2 years and asthma or hayfever at age 6–7 years combined. Methods Using a birth cohort of 620 infants with a family history of allergic disease born between 1990 and 1994, we examined risk of eczema or allergic sensitization (SPT > 3 mm to at least one of cow's milk, egg white, peanut, house dust‐mite, rye grass, and cat dander) by age 2 and asthma or hayfever at age 6–7. Daily ambient levels of pollen were measured during this period. Results Cumulative exposure to pollen concentrations up to 6 months was associated with aeroallergen sensitization with the highest risk occurring at 3 months (aOR = 1.34, 95% CI 1.06–1.72). Cumulative exposure to pollen up to 3 months was also associated with hayfever (aOR = 1.14, 95% CI 1.009–1.29) and between 4 and 6 months exposure with asthma only (aOR=1.35, 95% CI 1.07–1.72). Conclusion Persistent pollen exposure in infancy appears to increase the risk of asthma and hayfever in children. These results support the hypothesis that there is a critical window of opportunity in early development which may be important for modification of allergic outcomes.